"Arabized word" in the old linguistic lesson - Ibn Qutayba as a model - - Ghedjati, Abdessalam (Journal of Human Sciences, 2021)
This article deals with the "Arabized word" as one of the manifestations of Arabic contact with other neighboring languages. Since the language fulfills the function of communication between its users, it is susceptible to be influenced by them, since the interaction between it and them leads to the enrichment and development of the linguistic aspect. If it was normal for linguistic ties to arise between neighboring nations, the effect of that was then manifested in the adding of foreign words into the original language, and each of the neighboring languages ​​took what it needed in terms of words and combinations. This study aims to trace the position of Arab linguists on the phenomenon of "the Intruder" in general, and the word "Arabized" in particular, then to examine Ibn Qutayba’s approach in dealing with "Arabized" words in some of its linguistic heritage, as one of the pillars of the ancient linguistic lesson.